Crucial Interactions Between Selective Serotonin Uptake Inhibitors and Sigma-1 Receptor in Heart Failure - Md. Shenuarin Bhuiyan; Hideaki Tagashira; Kohji Fukunaga (Elsevier, 2013)
Depression is associated with a substantial increase in the risk of developing heart failure and is independently associated with increased cardiovascular morbidity and mortality. Inversely, cardiovascular disease can lead to severe depression. Thus, therapy with selective serotonin reuptake inhibitors (SSRIs) is strongly recommended to reduce cardiovascular disease-induced morbidity and mortality. However, molecular mechanisms to support evidence-based SSRI treatment of cardiovascular disease have not been elucidated. We recently found very high expression of the sigma-1 receptor, an orphan receptor, in rat heart tissue and defined the cardiac sigma-1 receptor as a direct SSRI target in eliciting cardioprotection in both pressure overload (PO)-induced and transverse aortic constriction (TAC)-induced myocardial hypertrophy models in rodents. Our findings suggest that SSRIs such as fluvoxamine protect against PO- and TAC-induced cardiac dysfunction by upregulating sigma-1 receptor expression and stimulating sigma-1 receptor-mediated Akt-eNOS signaling. Here, we discuss the association of depression and cardiovascular diseases, the protective mechanism of SSRIs in heart failure patients, and the pathophysiological relevance of sigma-1 receptors to progression of heart failure. These findings should promote development of clinical therapeutics targeting the sigma-1 receptor in cardiovascular diseases. Keywords:: cardiovascular disease, SSRI, hypertrophy, sigma-1 receptor, endothelial NOS